Phenylpropanoid amides from Solanum rostratum and their phytotoxic activities against Arabidopsis thaliana - Liu, Zhixiang; Ma, Xiaoqing; Zhang, Nan; Yuan, Linlin; Yin, Hongrui; Zhang, Lingling; An, Tong; Xu, Yubin (Frontiers in Plant Science, 2023)
Solanum rostratum, an annual malignant weed, has seriously damaged the ecological environment and biodiversity of invasion area. This alien plant gains a competitive advantage by producing some new phytotoxic substances to inhibit the growth of native plants, thus achieving successful invasion. However, the chemical structures, inhibitory functions and action mechanisms of phytotoxic substances of S. rostratum remain unclear. Phytochemical research on the whole plant of S. rostratum led to the isolation of four new phenylpropanoid amides (1−4), together with two known analogues (5−6). Their structures were identified by comprehensive HR-ESIMS, NMR and ECD data. All the compounds showed phytotoxic effects with varying levels on the seed germination and root elongation of one model plant (Arabidopsis thaliana), especially compound 2 and 4. Likewise, compounds 2 and 4 displayed potent inhibitory effects on antioxidant-related enzyme (POD). In addition, compounds 2 and 4 formed common conventional hydrogen bonds with residues Ala34 and Ser35 in POD revealed by molecular docking analyses. These findings not only helped to reveal the invasion mechanism of S. rostratum from the perspective of “novel weapons hypothesis”, but also opened up new ways for the exploitation and utilization of S. rostratum.